Unified biopolymer-based film design exploiting the multifunctional roles of tannic acid for beef preservation and real-time freshness monitoring - Jie Shi; Junjie Tang; Yingqi Zou; Xingyan Chen; Kaidi Zhao; Jianxi Zhang; Jie Pang; Honglin An; Bin Huang; Chunhua Wu (Food Research International, 2026)

Opposite effects of garlic essential oil and protein fertilizer on aerial hyphae outbreak of wine-cap mushrooms: Mechanisms involving the redox imbalance and membrane destabilization - Xinran Yin; HongLin An; Xiaoya Zhao; Hui Cui; Lei Yu; Yanan Sun; Weina Li; Demei Meng; Yang Nie; Xia Gao; Dan Zhu; Fansheng Cheng (Postharvest Biology and Technology, 2026)

Abscisic acid promotes sweet cherry fruit cracking dependent on cell wall disassembly - Ruie Liu; Li Wang; Zixing Sun; Zhuo Yan; Xiaojuan An; Wanxia Sun; Honglin Nong; Muhammad Usman; Zuoyan Qin; Songtao Jiu; Long Chen; Yaqin Wu; et al. (Food Research International, 2026)

Dual targeting of PI3K and mTOR induce necroptosis to enhance therapeutic efficacy in pancreatic neuroendocrine tumors - Jialing Pan; Mujie Ye; Jian'an Bai; Ruitong Xu; Lijun Yan; Jingtian Zhang; Hongbo Wang; Honglin Wang; Ye Tian; HongRu Zhang; Qiyun Tang (Chemical Engineering Journal, 2025)

Enhanced unprotected organic carbon in macroaggregates facilitates soil organic carbon accumulation following grazing removal in Tibetan alpine meadows - Xiang Liu; Zhiwen Ma; Wenping Qin; Xiaoyan Li; Hongxiao Shi; Bagen Hasi; Honglin Li; Zhifang An; Lihui Tian (Plant and Soil, 2025)

Discovery of the Miocene Yuanmou Conglomerate and Its Significance for the Drainage Evolution in the Southeastern Tibetan Plateau - Dai Zhang; Chang’an Li; Shitao Zhang; Honglin Yuan; Zengjie Zhang; Yawei Li (Journal of Earth Science, 2024)

Plant–Soil Moisture Positive Feedback Maintaining Alternative Stable States in the Alpine Marsh Ecosystem - Guorui Hu; Haonan Bai; Yunpeng Zhao; Ning Chen; Honglin Li; He Mao; Zengpeng Guo; Xiongjie Sheng; Hui Zhang; Hang An; Panhong Zhang; Zhengkuan Zhang; et al. (Ecology Letters, 2024)
A self‐reinforcing positive feedback is regarded as a critical process for maintaining alternative stable states (ASS); however, identification of ASS and quantification of positive feedbacks remain elusive in natural ecosystems. Here, we used large‐scale field surveys to search for ASS and a positive feedback mechanism under a wide range of habitats on the Tibetan Plateau. Using multiple methods, we proved that three stable states exist that accompany alpine marsh degradation. Positive feedbacks between changing soil moisture and plant community composition forced the ecosystem into another stable state, and the alteration of water use efficiency (WUE) of the component species contributed to this shift. This study provides the first empirical evidence that positive feedback loops maintain ASS in the alpine marsh ecosystem on the Tibetan Plateau. Our research revealed the powerful driving role of plants in transitions between states, which may support the conservation and restoration of global alpine marsh ecosystems.

Seasonal vertical distributions of diurnal variation of ice cloud frequency by CATS measurements over a global region (51°S-51°N) - Jin Wang; Honglin Pan; Dongliang An (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Simultaneous measurement of major, trace elements and Pb isotopes in silicate glasses by laser ablation quadrupole and multi-collector inductively coupled plasma mass spectrometry - Mengning Dai; Zhi’an Bao; Kaiyun Chen; Chunlei Zong; Honglin Yuan (Journal of Earth Science, 2017)